2014
DOI: 10.1016/j.ijid.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment experiences of pelvic bone hydatidosis

Abstract: Patients must be treated at the early stages of the disease. Total exeresis and individual reconstruction is necessary when osseous and soft tissue involvement is not extensive. Internal fixation should not be used when surgical eradication is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Recently, Liang et al reported a case series of nine patients with pelvic bone CE of whom two were treated with adjunct radiotherapy (cumulative dose 69 Gy in 23 fractions over 30 days) along with multiple surgical procedures and medical treatment. 21 No recurrence was observed over a followup of 4 and 6 years. However, as recurrence of disease may occur with considerable delay, follow-up needs to be conducted over many years, if not decades, to judge treatment efficacy.…”
Section: Available Clinical Data On Radiotherapy In Osseous Echinococmentioning
confidence: 86%
“…Recently, Liang et al reported a case series of nine patients with pelvic bone CE of whom two were treated with adjunct radiotherapy (cumulative dose 69 Gy in 23 fractions over 30 days) along with multiple surgical procedures and medical treatment. 21 No recurrence was observed over a followup of 4 and 6 years. However, as recurrence of disease may occur with considerable delay, follow-up needs to be conducted over many years, if not decades, to judge treatment efficacy.…”
Section: Available Clinical Data On Radiotherapy In Osseous Echinococmentioning
confidence: 86%
“…Solitary hydatid disease initially was not considered in the differential diagnosis primarily because of its sporadic occurrence in Austria (2009-2014: 7,2 reported cases per year) [3]. Most infections are diagnosed in immigrants from countries where this zoonosis is endemic such as the Mediterranean region [4,5].…”
Section: Background Discussion and Conclusionmentioning
confidence: 99%
“…Chronic infections of the bone, such as tuberculosis, as well as benign and malignant tumours, are considered in the differential diagnosis. Patients can be misdiagnosed even in endemic regions 3. Clearly, in Western countries where clinical suspicion is very low, this risk is even higher, especially taking into consideration the increasing immigration from endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients refuse amputation and are subject to less radical surgery, such as debridement, which is often combined with the use of local adjuvants such as hypertonic saline, formalin, phenol and polymethylmethacrylate 2 7. Osteosynthesis of pathological fractures and reconstruction with prosthesis has been described, when limb-sparing surgery is chosen 2 3 8. Collectively, amputation has been used in less than 1% of bone hydatidosis, mainly because the majority of patients present with limited disease.…”
Section: Discussionmentioning
confidence: 99%